Communication of Da'wah in Religious Moderation at Islamic Boarding Schools - Muhammad Husna Hisaba (SENTRI: Jurnal Riset Ilmiah, 2025)
Da’wah communication plays a strategic role in instilling moderate religious values in Islamic boarding schools to prevent the penetration of extremist ideologies that contradict the principle of rahmatan lil'alamin. However, there are still limitations in studies describing how moderate da’wah messages are constructed and conveyed systematically in traditional Islamic educational environments. This study aims to analyze da'wah communication practices at the Al-Ishlah Bobos Cirebon Islamic boarding school through David K. Berlo's communication model (SMCR), covering the source of the message (da'i), the content of the message, the media, and the reception of the mad'u. The research uses a qualitative descriptive method with an interpretive constructivist paradigm. The results show that da'wah communication is carried out through the approaches of da'wah bil-lisan, bil-qalam, and bil-hal, with messages emphasizing the values of tawassut (middle way), tawazun (balance), and tasamuh (tolerance). The media of da’wah included formal education, halaqah bahtsul masail, and digital platforms. Practically, this study reinforced persuasive da’wah strategies in Islamic boarding schools, while theoretically contributing to the development of studies on moderate da’wah communication based on communication models.